Long-Term Renal Outcomes and Safety Profile of Non-Steroidal Mineralocorticoid Receptor Antagonists in Non-Diabetic Chronic Kidney Disease: A Retrospective Cohort Study - Novia Wira Tungadi (HM Publisher, 2026)
Non-steroidal mineralocorticoid receptor antagonists, specifically finerenone, have demonstrated profound cardiorenal protective effects in diabetic kidney disease. However, their efficacy and safety in non-diabetic chronic kidney disease remain inadequately characterized, particularly within Southeast Asian populations experiencing high rates of hypertensive nephrosclerosis. A retrospective cohort study was conducted at a tertiary hospital in Makassar, Indonesia, evaluating 148 adult patients with non-diabetic chronic kidney disease (stages 3-4) who received finerenone between January 2022 and December 2024. Clinical data, including urinary albumin-to-creatinine ratio (UACR), estimated glomerular filtration rate (eGFR), and serum potassium, were analyzed using generalized and piecewise linear mixed-effects models over 24 months. The cohort (N=148) demonstrated a significant reduction in median UACR from a baseline of 845 mg/g to 460 mg/g at 24 months (p < 0.001). Following an initial hemodynamic eGFR dip in the first six months, the chronic annualized slope of decline stabilized at -2.2 mL/min/1.73 m² per year (95% CI: -2.8 to -1.6). Mild hyperkalemia occurred in 16.2% of patients, and moderate-to-severe hyperkalemia in 4.1%. Concomitant sodium-glucose cotransporter-2 inhibitor (SGLT2i) use was associated with a lower risk of incident hyperkalemia (OR 0.45, 95% CI 0.22-0.89). In conclusion, in this real-world observational cohort, adding finerenone to standard care in non-diabetic CKD patients was associated with significant reductions in UACR and an attenuation of eGFR decline over 24 months, alongside a manageable safety profile. These findings warrant further investigation in large, randomized trials.